Chemical characterization of leonardite and its potential use as soil conditioner and plant growth enhancement - Chanyut Ratanaprommanee (2018)
© 2017, Khon Kaen University,Research and Technology Transfer Affairs Division. All rights reserved. Humic substances which are major component of natural organic matter (NOM) play a major role through their impacts on soil fertility (physical, chemical, and biological soil properties) and plant development. Concerns about soil and environmental degradation caused by intensive high-input agriculture stimulated substantial efforts to increase organic matter particularly humic substances in the soils. Leonardite is NOM which contains high amount of humic substances particularly humic acid. Leonardite from various deposits in Thailand was examined as a potential NOM for soil improvement. Chemical compositions of leonardite varied from deposit to deposit. Leonardite from Lee mine contained the highest amount of humic acid (39.19 to 85.05%). Plant nutrients elements contained in all the leonardite samples were quite high (N, K, S, Ca, Mg, Fe, Zn and Mn) except for phosphorus. Characterization of leonardite samples by X-ray diffraction (XRD) and X-ray fluorescence spectrometry (XRF) showed that silica (Si) was the major element. High plant nutrients and humic acid content in leonardite samples indicated its high possible use to improve organic matter, humic acid and some plant nutrient levels in the soils. However, the very low pH values (1.84 to 2.55) and low P content (28.6 to 211.2 mg kg-1) of most leonardite samples should be raised before use. The information obtained from our study would be useful for appropriate use of leonardite in agriculture. In addition, with layer structure, high humic acid and nutrients contents of leonardite, it could be also used as microbial carrier as well as peat. Further investigation should be performed to obtain maximum benefit from this natural organic material.